Aplasia Cutis Congenita as a Sole Manifestation of Congenital Varicella Syndrome. (21st July 2020) - Leung, Alexander K. C.; Leong, Kin Fon; Lam, Joseph M.
Abstract : Aplasia cutis congenita following maternal varicella is well known. On the other hand, aplasia cutis congenita as the sole manifestation of congenital varicella syndrome is very rare. A perusal of the literature revealed only one case. We report two infants with aplasia cutis congenita as the sole manifestation of congenital varicella syndrome.